Energy Efficiency and Indoor Environment Quality - González Lezcano, Roberto Alonso (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue addresses a topic of great relevance. In developed countries, there is a higher prevalence of people choosing to spend time indoors. Data show that the time a person spends at home ranges from 60% to 90% of the day, and 30% of that time is spent sleeping, though this varies depending on the individual. Taking into account these data, indoor residential environments have a direct influence on human health. Furthermore, in developing countries, significant levels of indoor pollution make housing unsafe, impacting the health of its inhabitants. Housing is therefore a key health factor for people all over the world: various parameters such as air quality, ventilation, hygrothermal comfort, lighting, physical environment, and building efficiency can contribute to healthy architecture; poor application of these parameters can result in conditions that negatively impact health.